Hadronic high-energy gamma ray emission from microquasars - Romero, Gustavo Esteban (2005)
We present a hadronic model for gamma-ray production in the microquasar LS I +61 303. The system is formed by a neutron star that accretes matter from the dense and slow equatorial wind of the Be primary star. We calculate the gamma-ray emission originating from pp interactions between relativistic protons in the jet and cold protons from the wind. After taking into account opacity effects on the gamma rays introduced by the different photon fields, we present high-energy spectral predictions that can be tested with the new-generation Cerenkov telescope MAGIC.